System for Ensuring Social and Economic Security of Industrial Sector - D. N. Shvaiba (Наука и техника)
Methodological basis for formation of system to ensure social and economic security make provisions for specific features of industrial sector. It is proposed to reflect specificity of its protection with the help of methodological and operational fundamentals. Methodological fundamentals have been formulated on the basis of functional specificity for ensuring social and economic security of the industrial sector which was determined with the help of research process. They create a perimeter for ensuring social and economic security which is formed by expectations of the society from defense system of the country’s industrial sector. Operational fundamentals complement functional specificity of the system for ensuring social and economic security through formation of a specific institutional framework. The framework includes the following components: modeling presupposing multivariance in escalation of adverse events in the industrial sector and methods for its evaluation; instrumental assistance which takes into account necessity for instrumental diversity in order to implement defense functions in changing criteria (environment of industrial sector functioning, its structure and state of inter-element relations); functional consistency as a requirement to balance targets for ensuring social and economic security of the industrial sector with objectives and values pertaining to formation of the country’s industrial sector which are fixed in program documents of the state.